Penerapan Penilaian Formatif Kurikulum Merdeka Belajar Pada Mata Kuliah Psikologi Pendidikan di UIAD Sinjai - Nurhayati, R.; Amin, Al; Nur, Taufiq; Nur, Makmur Jaya; Musdalifah, Musdalifah; Yuliana, Sri; Meutia, Lucia (Seutia Hukamaa Cendekia, 2024)
A formative assessment is carried out to integrate and improve the learning process and achieve learning goals. Formative assessment aims to improve the learning process and obtain feedback. Feedback is a crucial component of formative assessment. Lecturers use feedback to improve learning, communicate to students what they need to learn and provide learning opportunities. This research aims to describe how formative assessment is implemented in educational psychology courses at UIAD Sinjai and the obstacles to implementing formative assessment in educational psychology courses at UIAD Sinjai. This research is included in phenomenological research using a qualitative research approach. This research was conducted in May 2024. The subjects of this research were educational psychology lecturers and even semester students of educational psychology courses. Meanwhile, the object of the research is the application of formative assessment of the independent learning curriculum in educational psychology courses. The data collection technique used in this research is the interview method. The research instrument used was an interview sheet. The research results show that 1) the form of implementing independent curriculum formative assessment in educational psychology courses is by using various methods such as discussions, questions and answers, lectures, and assignments; 2) An obstacle in carrying out formative assessments with students is that students may be less active in asking and answering questions, and some may not even actively participate in discussions in the room.